Integrasi Realitas Immaterial Ke dalam Pengembangan Teori Manajemen Pendidikan Islam: Penelitian - Taufiqurrahman, Muhammad; Wardhana, Kautsar Eka; Kholifah, Yusnia Binti; Ridani, Ahmad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the integration of immaterial reality in developing the theory and practice of Islamic educational management. The dominance of secular and rational paradigms has marginalized spiritual and moral dimensions within educational systems. Through a literature study of recent books and journals, this research finds that implementing divine values such as sincerity, responsibility, and blessing strengthens the managerial orientation of Islamic educational institutions. Integrating immaterial reality not only enriches management theory but also fosters an organizational culture grounded in faith and morality. Therefore, Islamic educational management is expected to serve as an instrument of spiritual and social transformation in response to contemporary challenges.